2021
DOI: 10.3390/microorganisms9071390
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri BM53-1 Produces a Compound That Inhibits Sticky Glucan Synthesis by Streptococcus mutans

Abstract: Cariogenic bacteria, such as Streptococcus (S.) mutans and S. sobrinus, produce insoluble and sticky glucans as a biofilm material. The present study demonstrates that a lactic acid bacterium (LAB) named BM53-1 produces a substance that inhibits the sticky glucan synthesis. The BM53-1 strain was isolated from a flower of Actinidia polygama and identified as Lactobacillus reuteri. The substance that inhibits sticky glucan synthesis does not exhibit antibacterial activity against S. mutans. The cariogenic S. mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Moreover, L. reuteri BM53-1 was found to produce a short extracellular polysaccharide with a molecular weight of about 30 kDa that impeded the production of sticky β-glucans by S. mutans and consequently the biofilm formation. In particular, the authors suggested that it acts by lowering the expression of gtfD that is necessary to give sickness to insoluble glucans produced in large amounts during the initial attachment of S. mutans on the surface ( 57 ).…”
Section: Beyond Probiotics: Lactobacillus Derivativesmentioning
confidence: 99%
“…Moreover, L. reuteri BM53-1 was found to produce a short extracellular polysaccharide with a molecular weight of about 30 kDa that impeded the production of sticky β-glucans by S. mutans and consequently the biofilm formation. In particular, the authors suggested that it acts by lowering the expression of gtfD that is necessary to give sickness to insoluble glucans produced in large amounts during the initial attachment of S. mutans on the surface ( 57 ).…”
Section: Beyond Probiotics: Lactobacillus Derivativesmentioning
confidence: 99%
“…Second, this study only explored the effect of AS vicK on a single species of S. mutans , while the dental plaque biofilm in the oral cavity is a habitat for a variety of bacteria, and the interaction of multiple microorganisms affects the balance of the microecology. For example, Gtfs can bind to oral microbes such as Lactobacillus and Candida albicans ( C. albicans ), affecting their EPS production [ 53 , 54 ] and enhancing the cariogenicity of symbiotic biofilms [ 55 ]. The vesicles of S. mutans containing Gtfs can also increase C. albicans biofilm formation by increasing EPS production [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This gene also regulates bacterial adhesion to the tooth surface, aggregation and coaggregation of the bacterial cells, and the integrity and stability of the biofilm structure. Therefore, its suppression may be associated with reduced biofilm/plaque formation and, ultimately, caries control [4,5]. We employed qRT-PCR to examine the expression of gtfB in S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…Dental biofilm, or plaque, constitutes a favorable environment for the growth of many bacteria, among which Streptococcus mutans (S. mutans) are known to play an important role in developing dental caries. In addition to acidic metabolites, S. mutans produces GtfB, GtfC, and GtfD, which are glucosyltransferase (GTF) enzymes that synthesize intracellular and extracellular polysaccharides [3,4]. They are encoded by gtfB, gtfC, and gtfD genes, respectively.…”
Section: Introductionmentioning
confidence: 99%